A material model for lamination stacks based on rough contacts - Luchscheider, Vera; Willner, Kai; Maidorn, Mischa (2014 4th International Electric Drives Production Conference, EDPC 2014, 2014)
This contribution presents, how to identify a material model of a lamination stack. The contact behavior between the single sheets is nonlinear and influences the behavior of the whole stack. The Simulation of the contact behavior is performed with contact models for normal and tangential direction. Due to the fact that calculating all sheets with contact is computational very expensive, a FE2-method is presented. With this method the calculation of the stack's behavior is based on a representative volume element. Further it is possible to identify a material model for the whole stack, which has got a linear and a nonlinear part. The linear part is caused by the material of the sheet, whereas the nonlinear part is a result of the contact behavior.
Keywords: lamination stack; material model; multiscale homogenization; normal and tangential contact behavior

Analysis of the lamination stack influence on the stiffness of stator active component - Luchscheider, Vera; Willner, Kai (PAMM, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.FT-TM.analys_5

Computation of the effective lamination stack's behavior considering the contact simulation with a multi-scale homogenization - Luchscheider, Vera; Maidorn, Mischa; Willner, Kai (Joint 11th World Congress on Computational Mechanics, WCCM 2014, the 5th European Conference on Computational Mechanics, ECCM 2014 and the 6th European Conference on Computational Fluid Dynamics, ECFD 2014, 2014)
The influence of the lamination stack on the mechanical behavior of an electrical machine is significant, especially for lightweight designs. Information about the stack's behavior is relevant for a proper calculation of the whole motor. This behavior is dependent on the contact between the single sheets. This paper aims to show that the normal contact behavior can be simulated with the elastic model of Bush, Gibson and Thomas, a plastic term depending on deformation of the highest peaks and a viscous term. The tangential slip is described through a micro-macro model. These models can be used in a representative volume element and consequently for a multi-scale homoge-nization. A material model of the whole lamination stack can be identified by loading the representative volume element with different deformations.
Keywords: Contact mechanics; Homogenization; Lamination stack

Development of a contact and a material model of laminated stacks - Luchscheider, Vera; Willner, Kai; Maidorn, Mischa (Proceeding 3rd International Electric Drives Production Conferenz, 2013)
The paper presents measurements and simulations of the stiffness of lamination stacks, which is a relevant parameter for the construction of electric machines. Since the progressive stiffness behavior of a lamination stack is dominated by the contact between the single sheets, different contact models are presented, where the selection and combination of the contact models is based on experimental tests on simple stacks of typical sheet material. With the help of the contact models, a material model will be created using the method of multiscales. © 2013 IEEE.
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.FT-TM.develo_5
Keywords: contact behavior; hysteresis; lamination stack

Development of a contact model for an electric motor lamination stack - Luchscheider, Vera; Willner, Kai (ECCOMAS 2012 – European Congress on Computational Methods in Applied Sciences and Engineering, e–Book Full Papers, 2012)
For electric motors light weight construction is becoming increasingly important, therefore the dynamical behavior of the lamination stack has to be known. The stacking of a lot of sheets has a relevant influence onto the behavior of the whole motor due to significant contact characteristics between the sheets. In this paper quasi-static tests are performed to identify this characteristic. At first a load representing the packaging process is applied onto the stack. Thereafter a cyclic load is superposed to show the forces during the motors life. With these quasi-static tests elastic and plastic effects and a hysteretic behavior are detected. These nonlinearities are referring to the sheet's roughness, the surface waviness and the existence of a coreplate varnish. In the modeling of the stiffness the roughness parameters are used. Based on the quasi-static model and with dynamic tests it is possible to identify the dynamic characteristic of the lamination stack.
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.FT-TM.develo_8
Keywords: Contact mechanics; Lamination stack; Roughness

Development of a model to describe the stiffness of an electric motor lamination stack - Luchscheider, Vera; Willner, Kai; Maidorn, Mischa (Proceedings, 2nd International Electric Drives Production Conference (EDPC 2012), 2012)
A light-weight design is becoming increasingly important for electric motors. As a consequence, adequate knowledge of the mechanical behavior of the lamination stack is of prime importance, since the lamination stack has a significant influence onto the behavior of the complete motor due to the significant contact characteristics between the single sheets. Quasi-static tests are performed to identify this stiffness behavior. A load representing the packaging process is first applied onto the stack. A cyclic load is then superposed to simulate the forces during the motor lifetime. With these quasi-static tests a progressive stiffness behavior with elastic and plastic effects is identified. This non-linearity can be attributed to the sheet's roughness and surface waviness. Based on the identified contact stiffness, an improved simulation of the quasi-static behavior of an electrical motor is possible. © 2012 IEEE.
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.FT-TM.develo_3
Keywords: contact mechanics; lamination stack; roughness

Identification of the lamination stack's behavior simulated with a multi-scale homogenization using a progressive contact formulation - Luchscheider, Vera; Maidorn, Mischa; Willner, Kai (PAMM 2014, 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.FT.FT-TM.identi_8